Analysis of eighteen years of emergency events in Costa Rica: losses, affected people and associated indicators - Mata-Abdelnour, Erick (2025)
This article examines Costa Rica’s response capacity and impact quantification in emergencies, analyzing historical data on emergency declarations from 2005 to 2023. Open databases from the National Emergency Commission (CNE) are used to assess and compare emergency events, the extent of losses, affected sectors, and patterns associated with declared emergencies. A total of 38 emergency declarations were identified during the analyzed period, with a notable predominance of hydrometeorological events (68%). This type of emergency is not only the most frequent but also responsible for the largest economic losses, representing 5.4% of the country’s average Gross Domestic Product (GDP). Economic losses were quantified at ₡2.341 billion, with the road and bridge sector being the most affected (33% of total losses). Geographically, the Pacific and Northern regions had the highest number of declarations, highlighting their vulnerability to these events. The article emphasizes the need for a robust emergency management system that not only responds effectively to crises but also enables better planning and resource allocation. This approach is crucial to increasing infrastructure resilience and mitigating the economic impact on the population, where annual losses can range from 7% to 20% of the GDP allocated to key sectors such as education and health.